Vital Subjects: Race and Biopolitics in Italy - Welch, Rhiannon Noel (Liverpool University Press, 2016)
Drawing on a range of canonical and non-canonical literary, cinematic and social scientific texts produced in post-Unification Italy, Vital Subjects: Race and Biopolitics in Italy is an interdisciplinary study of how racial and colonial discourses shaped the "making" of Italians as modern political subjects in the years between its administrative unification (1861-1870) and the end of the First World War (1919). The book includes readings of texts by Italian thinkers such as Leopoldo Franchetti and Paolo Mantegazza and it offers new readings of well- and lesser-known texts by a writer who has become Italy's most infamous precursor to Mussolini: poet, novelist, and political provocateur Gabriele D'Annunzio. Vital Subjects concludes with an original analysis of an early film that figures prominently in the history of cinema: Giovanni Pastrone's 1914 silent film Cabiria--produced in the wake of the Italian invasion of Libya (1911-12) and celebrating ancient Roman imperialism.